Outcomes of immunosuppression minimization and withdrawal early after liver transplantation. Issue 5 (31st December 2018) - Shaked, Abraham; DesMarais, Michele R.; Kopetskie, Heather; Feng, Sandy; Punch, Jeffrey D.; Levitsky, Josh; Reyes, Jorge; Klintmalm, Goran B.; Demetris, Anthony J.; Burrell, Bryna E.; Priore, Allison; Bridges, Nancy D.; et al.
Abstract : The Immune Tolerance Network ITN030ST A‐WISH assessed immunosuppression withdrawal in liver transplant recipients with hepatitis C or nonimmune nonviral liver disease. Of 275 recipients enrolled before transplantation, 95 were randomly assigned 4:1 to withdrawal (n = 77) or maintenance (n = 18) 1‐ to 2‐years posttransplant. Randomization eligibility criteria included stable immunosuppression monotherapy; adequate liver and kidney function; ≤Stage 2 Ishak fibrosis; and absence of rejection on biopsy. Immunosuppression withdrawal followed an 8‐step reduction algorithm with ≥8 weeks per level. Fifty‐two of 77 subjects (67.5%) reduced to ≤50% of baseline dose, and 10 of 77 (13.0%) discontinued all immunosuppression for ≥1 year. Acute rejection and/or abnormal liver tests were treated with increased immunosuppression; 5 of 32 rejection episodes required a methylprednisolone bolus. The composite end point (death or graft loss; grade 4 secondary malignancy or opportunistic infection; Ishak stage ≥3; or >25% decrease in glomerular filtration rate within 24 months of randomization) occurred in 12 of 66 (18%) and 4 of 13 (31%) subjects in the withdrawal and maintenance groups. Early immunosuppression minimization is feasible in selected liver recipients, while complete withdrawal is successful in only a small proportion. The composite end point comparison was inconclusive for noninferiority of the withdrawal to the maintenance group. Abstract : The ITN030ST A‐WISH immunosuppression withdrawal study demonstrates that early posttransplantation immunosuppressant minimization is feasible but complete withdrawal is rarely successful.